2016
DOI: 10.1097/mbp.0000000000000157
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between 25-hydroxyvitamin D levels and ambulatory arterial stiffness index in newly diagnosed and never-treated hypertensive patients

Abstract: Arterial stiffness measured by AASI in newly diagnosed and untreated patients with essential hypertension were significantly related to vitamin D levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
0
1
Order By: Relevance
“…A negative relation between PWV and augmentation index and vitamin D was found in healthy adolescents [31], adolescents with diabetes mellitus [31] and children with chronic kidney disease [32]. Also, contrary to our results, Turkish authors [33] found a negative relation (r = -0.385, p < 0.001) between vitamin D status and AASI in adults with newly diagnosed hypertensive adults.…”
Section: Discussioncontrasting
confidence: 99%
“…A negative relation between PWV and augmentation index and vitamin D was found in healthy adolescents [31], adolescents with diabetes mellitus [31] and children with chronic kidney disease [32]. Also, contrary to our results, Turkish authors [33] found a negative relation (r = -0.385, p < 0.001) between vitamin D status and AASI in adults with newly diagnosed hypertensive adults.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our findings, an observational study conducted among 544 healthy participants aged 20-79 years in the US showed an association between vitamin D insufficiency and increased arterial stiffness [50]. Similar findings regarding the association between 25(OH)D levels and arterial stiffness were also observed in two out of three smaller-scale observational studies conducted in Canadian, Turkish and Chinese populations (n=123-175) [51][52][53][54].…”
Section: Vitamin D and Pasisupporting
confidence: 90%